PENGARUH PARTISIPASI ANGGARAN, INFORMASI ASIMETRI, PENEKANAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KESENJANGAN ANGGARAN (Penelitian pada OPD Pemerintahan Kabupaten Indragiri Hulu) - Wahyud Hari; Agusti Restu; Paulus Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of budget participation, information asymmetry, budget emphasis, and clarity of budget targets on budget gaps in the OPD of the Indragiri Hulu Regency Government. The population in this study is the Regional Apparatus Organization (OPD) in Indragiri Hulu Regency totaling 30 OPD consisting of the secretariat, Inspectorate, Agency, Service. Data was collected by distributing questionnaires given to 90 respondents. The analytical tool used is multiple linear regression analysis using SPSS version 23 program. The results of this study indicate that Budget Participation, Information Asymmetry, Budget Emphasis, and Clarity of Budget Targets have a significant effect on Budgetary Gaps.Keywords: Budget Participation, Information Asymmetry, Budget Emphasis, Clarity of Budget Targets, Budgetary Gaps.